Modeling the Temperature Field in a Drill Under Influence of High-Frequency Current Hardening - Saidova Mukhabbat Khamroevna; Ergasheva Surayyo Rakhmonovna (Zien Journals, 2022)
The article presents an analysis of the main structural changes associated with temperature changes under the action of surface hardening by high-frequency currents on the drill surface
Keywords: hardening; heat treatment; model; temperature